Children's Afterschool Culinary Education Improves Eating Behaviors - Susanne Schmidt; Martin W. Goros; Jonathan A. L. Gelfond; Katherine Bowen; Connie Guttersen; Anne Messbarger-Eguia; Suzanne Mead Feldmann; Amelie G. Ramirez; Amelie G. Ramirez (Frontiers in Public Health, 2022)
Objective(s)Culinary education may be one way to improve children's eating behaviors. We formatively evaluated the effect of a hands-on afterschool 12-module, registered dietitian-led culinary education program on healthy eating behaviors in a predominately Hispanic/Latino, low-socioeconomic community.MethodsOf 234 children participating in the program, 77% completed both pre- and post-assessment surveys (n = 180; mean age 9.8 years; 63.3% female; 74.3% Hispanic/Latino, 88.4% receiving free/reduced lunch). In addition to program satisfaction, we assessed changes in children's self-reported fruit, vegetable, and whole-grain consumption, knowledge, and culinary skills using binary and continuous mixed effects models. We report false discovery rate adjusted p-values and effect sizes.Results95.5% of participants reported liking the program. Improved whole grain consumption had a medium effect size, while effect sizes for whole grain servings and vegetable consumption were small, but significant (all p < 0.05). Culinary skills increased between 15.1 to 43.4 percent points (all p < 0.01), with medium to large effect sizes.Conclusion(s)The program was well-received by participants. Participants reported improved eating behaviors and culinary skills after program completion. Therefore, this hands-on afterschool culinary education program can help improve healthy eating in a predominantly Hispanic/Latino, low-socioeconomic community.